Kendala Dalam Pengembangan Ekowisata Di Desa Selumbung, Kecamatan Manggis, Kabupaten Karangsem - Swabawa, I Made Abdi; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA, 2022)
One of the disposed in development of global tourism nowdays is powerful of phenomenon to traveled back to nature. Selumbung Village is a village that has potential to be developed into a tourist visiting area based on ecotourism. The purpose of this research is to identify the potential of ecotourism that can be used as tourist attractions and constraints of ecotourism development in Selumbung Village. Data collection techniques used in this research is observation, interviews, and documentation. ques. The determination technique of informant uses in this research is a purposive sampling. The data analysis technique used in this research is a qualitative data analysis technique. Selumbung Village located in Karangasem Regency has a lot of natural potential that can be developed into ecotourism. The potential of Selumbung Village is two waterfalls, cocoa plantations, a place of making sculptures, beekeeping and a place for making wood carvings. There are obstacles faced in developing ecotourism in Selumbung Village, including facilities and infrastructure, promotional media to inform about the potential of nature, culture, local wisdom, and lack of understanding for local communities in managing existing resources. These factors are a problem for the development and management of ecotourism in Selumbung Village. Keyword: Potency, development, ecotourism